Mobile product costing study of an Asian mobile operator. - Cheong, Tuck Meng. (2008)
The paper is based on a case study of a renowned Asian mobile network operator that has engaged BearingPoint to develop an actual mobile product offering costing study in a pilot project for Model one of their provincial network (with about 5 million subscribers) in response to a highly competitive open market public policy.